Belief-justification of intuition-based beliefs - Chen, Yi (Nanyang Technological University, 2021)
This paper makes a case for belief-justification of beliefs grounded in intuitions. When the beliefs we hold are intuitive in nature, one might ask whether those beliefs can be justified beliefs when (1) there is seemingly no rationale behind those beliefs and (2) the reliability of intuitions can be questionable. This paper identifies and distinguishes between two types of intuition—Types I (perceptual) and II (inferential)—and attempts to identify the source(s) of intuitions and its mechanism. Borrowing from Aristotle’s notion of the fully virtuous agent and Karen Jones’ model of local and global expertise, this paper turns to “experts” to establish the standard for reliability of intuitions and develops an evaluation system for the reliability of (the layman’s) intuitions. The system is supported by four conditions which allow for a more objective assessment of the reliability of intuitions. The paper concludes that intuitions can be reliable, and therefore beliefs that result from intuitions can be justified beliefs.